PRODUKTIVITAS DAN EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI JAGUNG DI KECAMATAN LUBUK PINANG KABUPATEN MUKOMUKO PROVINSI BENGKULU - Kurniati, Novitri; Hasanawi; Fitriani, Dwi (Agripita Publisher, 2017)
Corn (Zea mays) is one of the strategic commodities for a food-producing carbohydrates after rice. Beside that, corn is also used as animal feed, extracted oil, made of flour, and industrial raw materials. Obstacles encountered in increasing the productivity of corn are limited farmers in the allocation of factors of production, so that productivity is not optimal. This research obtain to determine the factors affecting productivity and efficiency of production factors on corn farming in District Lubuk Pinang Mukomuko. The method used is a survey method. Locations were selected purposively in Lubuk Pinang district Mukomuko. This research was conducted in June-August 2016. The sampling technique using proportional random sampling. Data analysis techniques to identify factors that affecting the productivity of corn used Cobb-Douglass production function and to analyze the efficiency of production factors used allocative efficiency. The results showed that with all the factors of production used very significant effect on the productivity of corn, while individually the factors of land, seeds, urea and Phonska very significant effect, whereas the amount of pesticides and labor not significant effect to the productivity of corn. The use of production factors pesticides and labor inefficient , while the use of land area, number of seeds, fertilizers urea and phonska under efficient.